Hukum Adat Bali di Tengah Arus Budaya Global dan Modernisasi Pembangunan - Maria Dominika Melani Hastuti (Jurnal Hukum Lex Generalis, 2023)
Balinese customary law is still very thick with elements of Hinduism and becomes a legal system that until now is still applied by indigenous peoples in Bali. The era of globalization brought social change to the indigenous peoples of Bali and caused the law to not only regulate the lives of traditional peoples but also regulate modern society in Bali. The results stated that the Balinese law of Awig-Awig is dynamic in the face of social change. Revitalizing Bali's systematic and structured customary law strengthens the Balinese indigenous people's existence so that it will be used as the primary consideration in decision-making made by the government.